2017
DOI: 10.1002/clen.201700329
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and Co‐Metabolism of Monochlorophenols and 2,4‐Dichlorophenol by Microbial Consortium

Abstract: In the present study, biodegradation of monochlorophenols (MCPs) and their co‐metabolism with 2,4‐dichlorophenol (2,4‐DCP) using mixed microbial consortium has been reported. The mixed consortium has shown 44 to 100% degradation of 50 to 300 mg L–1 3‐chlorophenol (3‐CP). While in case of 4‐CP, the degradation observed was 46 to 100% of 100 to 600 mg L−1 of initial concentrations. HPLC and spectrophotometric analysis indicated that the degradation occurred via a meta‐cleavage pathway. 4‐Chlorocatechol was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…2,4-Dichlorophenol (2,4-DCP) has been widely used as a fungicide, pesticide, and wood preservative [4], being released in high amounts into the environment (ca. 10,000 kg in the US during 2014) according to the United States Environmental Protection Agency (US EPA), who listed it as a priority pollutant among other CPs [2,5]. Human exposure to CPs takes places by consuming substances that contain them or through skin [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4-Dichlorophenol (2,4-DCP) has been widely used as a fungicide, pesticide, and wood preservative [4], being released in high amounts into the environment (ca. 10,000 kg in the US during 2014) according to the United States Environmental Protection Agency (US EPA), who listed it as a priority pollutant among other CPs [2,5]. Human exposure to CPs takes places by consuming substances that contain them or through skin [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bioremediation is the use of living organisms in order to remove pollutants from soil and water; a method that is considered more cost-effective and environmentally friendly than the conventional techniques mentioned above [5,8]. Microorganisms—mainly bacteria and fungi—indigenous to the contaminated regions are potential candidates for the task, benefiting from their acquired enzymatic arsenal, aiming to use the contaminants as food, ideally towards their complete mineralization [10].…”
Section: Introductionmentioning
confidence: 99%
“…This observation probably can be attributed to cometabolism, whereby the presence of one hydrocarbon accelerated the degradation of a more recalcitrant hydrocarbon (Hazen, ). Patel and Kumar () demonstrated that a microbial consortium degraded 2,4‐dichlorophenols better in the presence of monochlorophenol, probably due to the similar structure of both compounds initiating common degradative pathways. Khan, Hamayun, Bibi, and Sherwani () similarly reported a 24% increase in bacterial growth in a culture containing complex pyrene (four ring) with hydrocarbons of similar ring structure such as naphthalene (two ring), anthracene (three ring), and phenanthrene (three ring), compared to growth on pyrene alone.…”
Section: Resultsmentioning
confidence: 99%
“…However, many studies observed the remarkable ability of microorganisms to co-metabolize these emerging pollutants in the presence of easily biodegradable organic carbons. Cometabolism is often observed when certain compounds exhibit structural similarity to others that microorganisms are capable of degrading [124][125][126] .…”
Section: Mixed-substrate Utilizationmentioning
confidence: 99%